PERSEPSI SISWA SMAN 4 PEKANBARU MENGENAI PEMBERITAAN MEDIA ONLINE TENTANG PELECEHAN SEKSUAL DI FISIP UNIVERSITAS RIAU - Dwi Safitri; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Online media coverage of sexual harassment at the Faculty of Social and Political Sciences, Riau University, which was widely spread on various websites and social media led to the formation of opinions from students regarding this matter. Many opinions and judgments have sprung up on the news. In the process of forming the perception there are stages in the formation. Due to this, this study aims to see how the process of forming students' perceptions of SMAN 4 Pekanbaru. Starting from sensation, attention and interpretation. This study uses a qualitative descriptive method in determining the informants using purposive techniques so that 9 informants were found who met the criteria that the researchers had determined previously. The data collection techniques in this study were observation, documentation and interviews. Then the data obtained were analyzed by reducing the data, presenting the data and drawing conclusions. While the technique of checking the validity of the data in this study is triangulation and member check. The results in this study indicate that the process of forming students' perceptions of SMAN 4 Pekanbaru regarding online media coverage of sexual harassment at Fisip, Riau University is a sensation, namely online media coverage spread across various platforms such as Instagram, internet, YouTube and line today. Attention is location, time and actor. Interpretation is that this incident has a negative impact on the victim in which the victim will experience trauma. Due to this, this case must be processed to completion in accordance with applicable law until an acceptable result is obtained so that there is no dispute between the two parties.